Phase transitions in octanethiol-capped Ag nanocluster microfilm assemblies - Ellis, A.; D'Arcy-Galla, J.; Vijayamohanan, K.; Goswami, R.; Ganesan, P. G.; Ryu, C.; Ramanath, G. (Thermochimica Acta, 2005)
We describe phase transitions in microfilm assemblies of octanethiol (OT)-capped 2-4 nm-diameter Ag nanoclusters prepared from solutions with OT/Ag+ ratios of similar to50. Using DSC we observe two melting/crystallization-type reversible phase transitions: one at similar to61 degreesC due to interdigiated unattached octanethiol, and the other at similar to125 degreesC due to the phase comprised of the assembly of OT-capped nanoclusters. Increased thermal fluctuations weaken the inter-chain hydrophobic interactions between interdigitated OT molecules, leading to both phase transitions. The thiolate bond of OT-molecules bound to Ag nanoclusters are more rigid, thereby requiring a higher temperature to increase the flexibility of the alkyl chain of OT, and to melt the nanocluster assembly. The mobility of the nanoclusters in the melt is limited, and morphological features of the original assemblies are retained during recrystallization. No observable mass loss is detected up to similar to180 degreesC, above which OT molecules desorb from the Ag nanoclusters. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: differential thermal analysis; infrared spectroscopy; phase transitions; silver nanoclusters

Rapid hydrothermal synthesis route for nanocrystalline SrZrO3 using reactive precursors - Athawale, Anjali A.; Chandwadkar, Asha J.; Karandikar, Prashant R.; Bapat, Malini S. (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
Synthesis of nanocrystalline, orthorhombic (space group Pnma) SrZrO3 was achieved using appropriate molar proportions of nitrate salts of strontium and zirconium as precursors. Formation of SrZrO3 (SZ) was facilitated hydrothermally in time period as less as half-an-hour, in aqueous medium with alkaline pH as confirmed by XRD. Sample characterization was performed by FT-IR spectroscopy; powder XRD, SEM, TEM and DSC. The results have been explained by proposing a suitable reaction mechanism based on the step-wise analysis of the reaction intermediates using FT-IR as well as XRD. A double cation hydroxide composite formation is anticipated that under hydrothermal conditions results in the formation of SrZrO3. Morphology of the samples was determined with the help of SEM and TEM. The particle size distribution as seen from the TEM micrograph lies in the range of 15-25 nm. Heats of reaction for different decomposition steps were obtained by DSC. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Crystallization; diffraction; Electron microscopy; infrared spectroscopy

Synthesis, characterization, and acoustic properties of new soluble polyurethanes based on 2,2 `-[1,4-phenylenebis(nitrilomethylylidene)diphenol and 2,2 `-[4,4 `-methylene-di-2-methylphenylene-1,1 `-bis(nitrilomethylylidene)]diphenol - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Eight novel polyurethanes based on 2,2'-[1,4-phenylenebis(nitrilomethylylidene)]diphenol and 2,2-[4,4'methylene-di-2-methylphenylene-1,1'-bis(nitrilomethylylidene) ]diphenol acting as hard segments with two aromatic and two aliphatic diisocyanates (4,4'-diphenytmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) were prepared and characterized with Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1-NMR and C-13-NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis. All the polyurethanes contained domains of semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties and solubility parameters were calculated with the group contribution method. (c) 2007 Wiley Periodicals, Inc.
Keywords: infrared spectroscopy; NMR; phase behavior; polyurethanes; Thermal properties

Studies on the effect of glass transition on the crystalline transition in syndiotactic polystyrene - solvent complexes - Naidu, Sudhakar; Ramesh, N. C. (Macromolecular Symposia, 2008)
Amorphous syndiotactic polystyrene (sPS) was crystallized at room temperature in Norbornadiene (bicyclo[2,2,1]-hepta-2,5-diene), Mesitylene (1,3,5-Trimethyl benzene), 3-Carene (3,7,7-trimethyl bicyclo[4,1,0]hept-3-ene) and DMN (1,4-Dimethylnaphthalene) to form the sPS-solvent complex (h form) with respective solvent molecules. In situ HTFTIR studies showed that the delta form to gamma form transformation temperature occurs well below the glass transition temperature of sPS, which is depressed due to the presence of solvent in the amorphous phase; higher the solvent content in the complex, lower the transition temperature. Glass transition temperatures determined by Modulated differential scanning calorimetry (MDSC) coincide with the transition temperatures, indicating that the delta form transforms into gamma form at the glass transition temperature for these complexes. Such a behavior is very different from the behaviour of the sPS- solvent complexes formed by dichloromethane, chloroform, toluene, o-dichlorobenzene, decalin (cis-trans) etc. and for these complexes the transition occur well above the T(g).
7th Conference on Polymer Solvent Complexes and Intercalates, Marrakech, MOROCCO, MAY 21-23, 2008
Keywords: Crystallization; glass transition; infrared spectroscopy; Syndiotactic polystyrene

Synthesis and FTIR spectroscopic investigation of the UV curing kinetics of telechelic urethane methacrylate crosslinkers based on the renewable resource-cardanol - Rekha, N.; Asha, S. K. (Journal of Applied Polymer Science, 2008)
UV curable telechelic urethane-methacrylate crosslinkers based on the natural resource-cardanol was synthesized in a one pot synthetic step involving end capping of isophorone diisocyanate with one equivalent of hydroxyethyl methacrylate followed by condensation with cardanol. The structures of the resins were characterized by H-1 and C-13 NMR, fourier transform infrared (FTIR) and Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) spectroscopies and size exclusion chromatography (SEC). The curing process and double bond conversion in presence of 2,2-diethoxy acetophenone as photo-initiator upon UV irradiation was followed by Fourier transform infrared spectroscopy. These hydrogen bonded crosslinkers based on cardanol and its derivatives had higher double bond conversion when compared to a nonhydrogen bonding standard such as hexanediol diacrylate (HDDA) under identical conditions. The temperature effects on the hydrogen bonding were investigated, and a decrease in the extent of double bond conversion with increase in temperature was observed for the telechelic urethane-methacrylate crosslinkers whereas a steady increase in the curing rate was observed for HDDA. This gives direct indication of the influence of hydrogen bonding on the curing process. (C) 2008 Wiley Periodicals, Inc.
Keywords: Cardanol; hydrogen bonding; infrared spectroscopy; renewable resource; UV curing

Magnetic studies of SiO2 coated CoFe2O4 nanoparticles - Limaye, M.V. (Journal of Magnetism and Magnetic Materials, 2017)
Oleic acid capped CoFe2O4 nanoparticles which exhibit a high coercivity of ∼9.47 kOe at room temperature were coated with a robust coating of SiO2. We have used chemical synthesis method to obtain SiO2 coated CoFe2O4 nanoparticles with different weight percentages of CoFe2O4 in SiO2 (1.5, 3.1 and 4.8 wt.%). The morphological investigation of the coated nanoparticles by transmission electron microscopy shows that the particles are spherical with average size ∼160 nm. Infrared spectroscopy reveals that oleic acid capping on the surface of CoFe2O4 nanoparticles is retained after silica coating process. The complete coating of SiO2 on CoFe2O4 nanoparticles is confirmed by X-ray photoelectron spectroscopy as there is no signature of cobalt or iron ions on the surface. Magnetic measurements show that coercivity of SiO2 coated CoFe2O4 particles remains more or less unaffected as in CoFe2O4 nanoparticles at room temperature. In addition, the temperature dependent magnetic measurements show that at 5 K the CoFe2O4 and SiO2 coated 1.5 wt.% CoFe2O4 samples exhibit a very high value of coercivity (∼20 kOe) which is more than twice as compared to room temperature coercivity value (∼9.47 kOe). We conclude that silica coating in our study does not significantly affect the coercivity of CoFe2O4 nanoparticles.
Keywords: Coatings; coercive force; High Resolution Transmission Elctron Microscopy; infrared spectroscopy; Magnetic materials